Calcium, actin and the spectrin skeleton: Responses to swelling and shrinking perturbations. - Herring, Tammy. (University of Ottawa (Canada), 1998)
It was postulated that cells regulate their surface membrane in response to membrane tension gradients. Increases in membrane tension, brought about by swelling, should therefore elicit addition of membrane to the cell surface, whereas decreases in membrane tension, brought about by shrinking, should cause retrieval of excess surface membrane. If increased membrane tension increases membrane area via enhanced calcium dependent exocytosis, then (Ca) $\rm\sb{int}$ rather than membrane tension may be the primary signal used in surface area regulation. (Ca) $\rm\sb{int}$ in swelling molluscan neurons was measured by FURA-2 ratiometric microscopy using perturbations which induced vacuole-like dilations (VLDs). (Ca) $\rm\sb{int}$ was measured in either normal (3.5mM) or low (0.5$\mu$M) extracellular calcium. The small but statistically significant changes observed were well below the levels which would stimulate exocytosis. In BAPTA loaded neurons, resting (Ca) $\rm\sb{int}$ was about one-half its normal value and did not change with osmotic perturbations. BAPTA was therefore effective at chelating neuronal intracellular calcium. BAPTA loaded neurons, like control neurons yielded VLDs using either normal or low extracellular calcium. Neurons incubated in cytochalasin, a drug that promotes actin depolymerization, do not undergo VLD recovery. Microscopy studies into how neuronal F-actin responded to osmotic perturbations and how the F-actin is related to VLDs were initiated. In Lymnaea neurons that had swelled then reshrunk to form VLDs, F-actin rapidly reorganized around the VLDs. At the substrate, F-actin formed rings of newly constituted leading edge (filopodia and lamellipodia) that we termed actipodia. Microinjection of live molluscan neurons with fluorescent G-actin also indicated that F-actin could reorganize as actipodia around the VLD membrane within 5 minutes. Cytochalasin incubated neurons formed VLDs but no actipodia were observed in association with these VLDs. F-actin rich actipodia may be the structures which help the VLD pinch off from the substrate and therefore begin reinternalization of excess surface membrane. (Abstract shortened by UMI.)
Keywords: Biology, Cell.